THE ROLE OF TAX ADMINISTRATION AND TAX RATE ON FOREIGN DIRECT INVESTMENT - Rusman Affandi Nasution (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2020)
This thesis examines the impact of the tax system in determining FDI inflows in countries around the world from 2010 to 2017. We group the countries into two groups, based on income levels. Our findings suggest that the tax system, which reflects the easiness of tax payment, and the commitment to all tax regulations, plays a significant role in determining FDI inflows in low & middle-income countries. In high-income countries, it is the corporate tax cut that plays the role. The result implies that improved institutional performance in low & middle-income countries is an essential factor to induce FDI inflows.